Implementation of the Concept of Islamic Criminal Responsibility in Indonesian Positive Law - Humairaharahap; Diana Sri Utami; Siti Hadijah; Cintami Grece NR; M. Rahman Rizki (ISNU Nine-Star Multidisciplinary Journal, 2024)
The positive legal system of Indonesia is not in line with the idea of ​​accountability from Jinayah. Criminal responsibility according to Islamic criminal law is based on the awareness and intention of the perpetrator (mens rea) and proof of the unlawful act (actus reus), which is in line with the principles of sharia. The purpose of this study is to study how the concept of Islamic criminal responsibility can be applied to Indonesian law by considering the principles of justice, humanity, and uniformity in accordance with the country's constitution. The research method used is normative, by looking at various laws in Indonesia and reading literature on Islamic criminal law and its implementation in countries with Islamic law. The results of the study indicate that, although there are fundamental differences between Islamic law and Indonesian positive law, some elements of the concept of Islamic criminal responsibility can be exploited, especially in cases containing certain crimes such as qisas, diyat, and ta'zir. By considering Pancasila as the philosophical foundation of the state, these elements can be exploited. It is hoped that this implementation will help strengthen the national legal system by providing space for the religious values ​​that live in it.